Immunologic characterization of a cloned fragment containing the species-specific epitope from the major outer membrane protein of Chlamydia trachomatis. - Toye, B (1990)
A 183-bp fragment encoding variable domain IV (VD IV) of Chlamydia trachomatis serovar B major outer membrane protein (MOMP) (amino acids 273 to 333) and containing the species-specific epitope was cloned and expressed in Escherichia coli as a fusion protein with Schistosoma japonicum glutathione S-transferase (GST-VD IV). The fusion protein was affinity purified under nondenaturing conditions and used to immunize rabbits. Antisera were characterized by microimmunofluorescence, immunoblot, dot blot, peptide enzyme-linked immunosorbent, and in vitro neutralization assays. Antisera recognized MOMP from all 12 tested serovars of C. trachomatis but not from Chlamydia psittaci. In a dot blot assay, antisera bound to elementary bodies of serovars B, D, E, L2, and K in a strong fashion and to elementary bodies of serovars F, G, A, and H in a weak fashion but not to elementary bodies of serovars C, J, and I. High-resolution peptide mapping with synthetic overlapping serovar B MOMP peptides in a solid-phase enzyme-linked immunosorbent assay showed that immunization with GST-VD IV produced a serologic response that closely mimicked the response produced with purified serovar B elementary bodies. Antipeptide antibodies with strong binding to species- and subspecies-specific epitopes were elicited. Antisera were able to neutralize only those C. trachomatis serovars that bound antibodies in the dot blot assay. These results suggest that antigenic fragments from VD IV containing the species-specific epitope may be useful in the construction of a chlamydial vaccine for some but not all C. trachomatis serovars.